Search Engine Optimization (SEO) dan Tantangannya pada Pemberitaan Good News from Indonesia (GNFI) (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
Competition in the media business is increasingly difficult as the number of online media grow and access to news becomes easier. Each media strives to maintain its existence and remain the public's preferred source of information, including Good News from Indonesia (GNFI). This article discussed GNFI's strategy through the application of search engine optimization (SEO) techniques and the challenges encountered in SEO update. Data were collected through observation, interview, and document review from January to August 2025. The results show that GNFI applied on-page and off-page SEO techniques as a strategy to increase visibility in search engines. The presence of an AI Overview posed a challenge in itself, as it could reduce the number of click view the news portal. The application of SEO techniques was not only a technical optimization strategy but also a form of media adaptation to the changing digital journalism landscape influenced by technological advances.